Development of Autocad 2D Learning Media with the ADDIE Model - Pujiastuti, Elfisana; Rufi’i, Rufi’i; Suhari, Suhari (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop AutoCAD 2D-based learning media for the Road and Bridge Construction subject for class XI DPIB students. The study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to draw and design bridges with learning media for SMK PPGRI 1 Gresik students. This research combines qualitative data analysis in the form of improvement suggestions and quantitative data obtained from questionnaires assessing the feasibility of the learning media by test subjects. After several validation and feasibility testing phases, the AutoCAD 2D learning media is deemed suitable for vocational school education. The developed learning media includes worksheets or jobsheets and a guide to using AutoCAD 2D software. Based on expert validation, the feasibility results show a 94.29% (very feasible) score for material validation. The design expert validation scored 90% (very feasible), the small group test resulted in 67% (feasible), and the significant group test achieved 96.8% (very feasible or excellent). Applying AutoCAD 2D in Road and Bridge Construction learning improves students' technical skills, making them more prepared for careers in design and construction. This innovation also ensures the learning's relevance to industry standards.